The Centre-Periphery Dichotomy in Davor Špišić’s Vuk na snijegu and Karin Peschka’s Autolyse Wien. Erzählungen vom Ende and its Turns in Times of Crisis - Marijana Mandić; Sonja Novak; Ljiljana Pıntarıć (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
The paper examines the way how the culture of the city is represented in contemporary German and Croatian prose exemplified by Karin Peschka’s Autolyse Wien. Erzählungen vom Ende [Autolysis Vienna. Stories of the End] and Davor Špišič’s Vuk na snijegu [Wolf in the Snow]. The thesis of the paper is that Peschka’s and Špišić’s literary cityscapes of Vienna and Zagreb respectively are self-referential semiospheres or metaphors produced by their cultures, whose semiotic textual spaces are formed holistically as results of the geocultural and sociohistorical context of centrality (Vienna) and periphery (Zagreb), and the way they correlate and interchange. By applying a (post) structuralist, comparative and sociological approach, the paper analyses how the represented city space is reshaped in the dystopian and post-apocalyptic narratives to a state of unrecognizability and is reconstructed by means of reception, experience and knowledge of the readers, e. g. by the end of the short stories’ collection Autolyse Wien Peschka’s Vienna remains alive only in the characters’ memories, while most parts of Špišić’s Zagreb are altered in terms of their function, character, purpose, and accessibility. On the one hand, this results in the loss of the represented city’s cultural and urban identity, and on the other, the dichotomy of centrality and periphery, the urban and the rural, the civilized and the wild, the cultured and the natural becomes blurred.